STRATEGII ALGORITMICE ŞI EURISTICE DE REZOLVARE A PROBLEMELOR - USM ADMIN (Moldova State University, 2009)
The successful solving of problems is influenced by the utilized strategies. The essence of the algorithmic and heuristic strategies, its applications in solving of distinct problems and, in particular, of the more difficult problems make up the object of the present research.